PENGARUH BUDAYA ORGANISASI, MOTIVASI KERJA, DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DI BAGIAN KEUANGAN SEKRETARIAT DAERAH KABUPATEN TABANAN - Gusti Ayu Putu Sri Suningsih; I.B. Darma Negara; Nengah Ganawati (Universitas Warmadewa, 2017)
Employee performance is the key to progress and success of the organization. Performance that is owned by the Organization on the fact of the matter is a result of work requirements to be met by employees. The company's performance is highly determined by the qualified employees. This research aims to know the role of disciplined employee in mediated influence of organizational culture, work motivation on performance employee in the financial section of the regional secretariat of the Tabanan Regency. The research method used is descriptive quantitative. Data processing technique using the analysis of Partial Least Squares (PLS) multivariate statistical techniques. The sample of this research was the performance of employees in the financial section of the regional secretariat of the Tabanan Regency as much as 85 respondents. Results of the study prove that organizational culture positive and significant effect against the discipline of work.organizational culture positive effect against the discipline of employees. Motivation work a positive and significant against the discipline pf work. A positive and significant effect of motivation against the performance of employees. The positive effect of work discipline against the performance of the employees, but not significant. The discipline of work is not mediation variables between the culture of the Organization against the performance of employees. The discipline of work is not a variable mediation between motivation on performance employee. To the employees of the Regional Secretariat of the financial part of Tabanan Regency recommended to further investigate the factors that affect performance, and the issue of what happened, and how should they fix the issue, thus achieved an optimal employee performance.